Self‐Supporting Iron‐Modified Nickel Phosphide Electrode Realizing Superior Bifunctional Performance for Water Splitting. Issue 4 (27th January 2023) - Chen, Pengzuo; Li, Kaixun; Ye, Yutong; Wu, Doufeng; Tong, Yun
Abstract: Utilizing non‐noble metal‐based materials to design highly active and low‐cost bifunctional electrocatalysts play a vital role in oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) for the overall water splitting. Herein, a self‐supporting nickel phosphide electrode with the decoration of FeOOH species is successfully prepared by a simple electrodeposition and maceration drying process. This kind of electrode exhibits superior bifunctional activity for both HER and OER. Benefiting from the more exposed catalytic active sites, open hierarchical structure, and better reaction kinetics. At the current density of 100 mA cm −2, the optimal Ni2 P−FeOOH/NF delivers the small overpotentials of 200 mV and 235 mV for HER and OER in an alkaline solution, respectively. After further assembling into the electrolyzer, the Ni2 P−FeOOH/NF‐based device shows a lower cell voltage of 1.5 V and 1.66 V to reach the current density of 10 mA cm −2 and 100 mA cm −2, along with superior stability. This work outlines a promising strategy for the facile preparation of self‐supporting electrodes for practical application in hydrogen generation by overall water splitting. Abstract : Water splitting : A self‐supporting nickel phosphide electrode with the decoration of FeOOH species is successfully prepared as superior bifunctional electrode for overall water splitting in an alkaline medium.